2019
DOI: 10.1080/0951192x.2019.1699257
|View full text |Cite
|
Sign up to set email alerts
|

Trust-based resource sharing mechanism in distributed manufacturing

Abstract: Manufacturing has moved from local towards global economy in the past decades enabling new paradigms to come into practice, such as distributed manufacturing which aims at increasing companies' flexibility with a decentralized system consisting of autonomous entities. In the paper, a distributed collaboration framework of manufacturing agents is introduced, where the members with resource shortages can request resources from others, divide requests among multiple agents, reorganize their production to be able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Second, the proposed consensus algorithm is included in the processes of resource division based on multi-agent systems [8]. Many of the proposed solutions in this field use blockchain technology [9], where we can apply the proposed consensus as each agent is a user participating in changing the content of the blockchain.…”
Section: Contributionsmentioning
confidence: 99%
“…Second, the proposed consensus algorithm is included in the processes of resource division based on multi-agent systems [8]. Many of the proposed solutions in this field use blockchain technology [9], where we can apply the proposed consensus as each agent is a user participating in changing the content of the blockchain.…”
Section: Contributionsmentioning
confidence: 99%
“…The problem of distributed manufacturing (DM) or production cooperation management within dynamic network forms has recently been undertaken by a considerable number of research and industrial groups. For example, some results of DM projects have been described for cluster network systems (Akoorie & Ding, 2009;Liu et al, 2017), additive manufacturing in car industry (Durão et al, 2016), metal industry (Gąbka & Susz, 2016), administration in networked headquarters industrial environments (Moghaddam et al, 2016), and sharing DM capacities in a crowdsourced way (Szaller et al, 2020a;Szaller et al, 2020b). Unfortunately, the research and implementation projects to be found in DM or distributed production (DP) management research bibliography and industrial reports basically do not have advanced (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that resource sharing organizations should be encouraged to keep their promises and to have commitments to their plans and goals. Trusting in each other's promises is one of the main pillars of collaboration, which also helps to increase the service level of the participants and to reduce risks [9] [10]. Nevertheless, computational models applying trustfulness in decision-making are mainly used only in computer technology and online commerce [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the first reference model -presented in [9], referred to as "Model A" -participants communicate and coordinate their actions directly with each other: they are sending resource requests to all the other organizations who are part of the federation. When receiving a request, all the participants being able to complete the request are applying for the given job and send offers to the requester.…”
Section: Introductionmentioning
confidence: 99%